The Effect of Vitamin C Supplementation on Chest X-Rayimprovementin Pulmonary Tuberculosis Patients During Intensive Phase in Medan - Budi Jefri; Bintang YM Sinaga; Parluhutan Siagian; Putri Chairani Eyanoer (Jurnal Respirologi Indonesia, 2020)
Backgrounds: Tuberculosis (TB) is still a public health problem in the world.Vitamin C is a water-soluble micronutrient, protects the host from reactive oxygen and reactive nitrogen intermediates generated during mycobacterial infection, involved in the synthesis of collagen, iron transport, and acts as physiological antioxidant. Vitamin C plays role in killing Mycobacterium tuberculosis by fenton reaction. This study was to determine the effect of vitamin C supplementation on chest X-ray (CXR) improvement in pulmonary TB patients during intensive phase. Methods: This was a quasy experimental study with single blind-randomized controlled trial design. Subjects were divided into 2 groups, first group was pulmonary TB patients treated with anti tuberculosis drugs (ATD) plus vitamin C and the second group was treated with ATD plus placebo. This study was conducted in several public health center in Medan City. The subjects were pulmonary TB patients with positive AFB sputum in intensive phase from December 2017 to May 2018. Data were analized using t-test dependent. Results: From 80 total subjects, 53 males (66%) and 27 females (34%). After 2 months of treatment, improvements in CXR images were found in the ATD plus vitamin C group, about 21 subjects (52.5%) had no more lesions on CXR, while the same condition was found on 15 subjects (37.5%) in the placebo group. Conclusion: Vitamin C supplementation in pulmonary TB provided better improvements of CXR images. (J Respir Indo. 2020; 40(2): 82-7)